Self-Esteem and Peer Pressure in Adolescent Males Using Drugs - Umme Amara; Rao, Sheeza; Siddiqui, Barerah (Applied Psychology Review, 2022)
The purpose of this study was to investigate the relationship between self-esteem and peer pressure in drug abusing male adolescents. In the light of earlier literature, it was hypothesized that there will be high prevalence of peer pressure and low self-esteem in adolescent males with drug abuse and there will be a negative relation between self-esteem and peer pressure in drug abusing male adolescents. For this study, 155 male adolescents (10 to 19 years) were chosen through convenient sampling from different drug rehabilitation centers in Karachi. The participants belonged from madrasa and school. Proper ethical considerations were maintained and permissions were taken from different rehabilitations centers for data collection. Adolescent Self Esteem Questionnaire and Peer Pressure Scale were used for this study. Findings indicated high prevalence of low self-esteem (44%) and consecutively high incidence of peer pressure (73.5%) in adolescent males with drug abuse. Moreover, the study proved that a significant negative relationship exists between self-esteem and peer pressure among adolescent males with drug abuse (r = -0.75, p = 0.05). The study has implications for psychologists, counselors, educationist and government for managing self-esteem and peer pressure in students